Comparison of determination of mechanical properties in reinforcing bars for concrete with axial extensometer conventional and laser extensometer - Monge Sandí, Ana Lorena (2025)
The current article describes the testing process and analysis of 40 deformed steel bars for concrete reinforcement, which where instrumented with a conventional extensometer and a laser extensometer simultaneously. A statistical analysis was used to determine the accuracy of the measurements and data calculated from the laser extensometer's output information in comparison with that of the conventional extensometer. The observed behavior determines that the laser extensometer indicates different results when used to determine the elasticity modulus, however, it does not lead to significant differences for the determination of all the mechanical properties required by the ASTM standards A615 and A706.